PLASTIC EXCISE TAX IN INDONESIA: FISCAL POTENTIAL AND SHORT-RUN ECONOMIC IMPACTS FROM AN INPUT–OUTPUT SIMULATION - Rheza Auliya Rahman (MUC Tax Research Institute, 2026)
Abstract Indonesia faces persistent marine plastic pollution and has considered a plastic excise tax as a fiscal instrument to control single-use plastic consumption. This study estimates the fiscal potential and short-run economy-wide impacts of plastic excise in Indonesia using an updated 2024 Input–Output framework. The 2016 Indonesian Input–Output table is updated through the RAS technique, while the policy shock is derived from an excise-induced price increase and plastic bag demand elasticity. The results show that, under a static baseline scenario, plastic excise could generate IDR 39.82 trillion in 2024 and IDR 40.69 trillion in 2026. However, after incorporating behavioural response, the IDR 200 tariff is estimated to reduce plastic bag consumption by 47.85%, equivalent to a final demand shock of IDR 38.11 trillion in 2024. The Input–Output simulation indicates a national output decline of IDR 73.47 trillion, a Gross Value Added contraction of IDR 32.23 trillion, and a factor income reduction of IDR 24.71 trillion. These findings suggest that plastic excise requires gradual implementation, revenue recycling, and transitional support for affected sectors to balance fiscal, environmental, and economic objectives in Indonesia. Abstrak Indonesia menghadapi persoalan pencemaran plastik laut yang terus berlanjut, sementara pemerintah mempertimbangkan cukai plastik sebagai instrumen fiskal untuk mengendalikan konsumsi plastik sekali pakai. Penelitian ini mengestimasi potensi penerimaan dan dampak ekonomi jangka pendek dari cukai plastik di Indonesia dengan menggunakan kerangka Input–Output 2024 yang diperbarui. Tabel Input–Output Indonesia 2016 diperbarui melalui teknik RAS, sedangkan guncangan kebijakan dihitung dari kenaikan harga akibat cukai dan elastisitas permintaan kantong plastik. Hasil penelitian menunjukkan bahwa, dalam skenario statis, cukai plastik berpotensi menghasilkan penerimaan sebesar Rp39,82 triliun pada 2024 dan Rp40,69 triliun pada 2026. Namun, setelah respons perilaku diperhitungkan, tarif Rp200 per kantong diperkirakan menurunkan konsumsi kantong plastik sebesar 47,85%, setara dengan guncangan permintaan akhir sebesar Rp38,11 triliun pada 2024. Simulasi Input–Output menunjukkan penurunan output nasional sebesar Rp73,47 triliun, kontraksi Nilai Tambah Bruto sebesar Rp32,23 triliun, dan penurunan pendapatan faktor produksi sebesar Rp24,71 triliun. Temuan ini menegaskan bahwa cukai plastik memerlukan penerapan bertahap, daur ulang penerimaan, dan dukungan transisi bagi sektor terdampak, khususnya industri plastik, kimia, perdagangan, transportasi, energi, dan layanan pendukung dalam rantai produksi nasional secara adil, terukur, dan berorientasi pada keberlanjutan jangka panjang.